Disaster communication uses field training exercise simulation as an important aspect of disaster risk reduction - Lestari, Puji; Ritonga, Rajab; Ruliana, Poppy; Br Barus, Catrinadia Christie (Penerbit Universiti Kebangsaan Malaysia, 2020)
Karo Regency, North Sumatra is an area prone to the eruption of Mount Sinabung that does not yet have a Contingency Planning policy. This research aims to find the communication model of the Mount Sinabung eruption disaster through a field training exercise simulation to test the Contingency Plan document before becoming policy. The method used is descriptive qualitative, with the object of research is the communication of Mount Sinabung eruption disaster. The research subjects were the Head of Sinabung Observation Post, the Head of BPBD, the Assistant Regent, the head of the Office of Communication and Information, journalists, victims, and volunteers. Data collection techniques carried out by in-depth interviews, observation, documentation, Focus Group Discussion, and field training exercise simulation. The data analysis technique was carried out qualitatively before simulation, during simulation, and after simulation. The results of the study were to find a communication model of the Mount Sinabung eruption disaster through a field training exercise simulation. This research contributes in the form of: (1) a new communication model in the process of reducing the risk of the eruption of Mount Sinabung through a field training exercise simulation which is considered effective in improving disaster-resilient communities; (2) new methods in disaster communication research, namely using data collection techniques through field training exercise simulation; and (3) The new Karo Regent Regulation Number 08/2020. This finding can be adopted for reducing the risk of other volcanic disasters.